(untitled) (Gestão & Regionalidade, 2024)
This work proposes to measure the level of sustainable human development for 57 countries and eight economic blocs, considering the year 2014. Specifically, it is intended to rate which countries and economic blocs develop in a sustainable way. For this, the Environmental Index (EA) was constructed, as proposed by Blancard & Hoarau (2013) and Chansarn (2014), using the Data Envelopment Analysis (DEA). Subsequently, the Sustainable Human Development Index (SHDI) was measured, considering the geometric mean of the three dimensions of the HDI and EA, according to the formulation suggested by Blancard & Hoarau (2013) and Bravo (2014). The results indicated that, in general, nations have achieved high EA and experienced improvements in their well-being. Therefore, is concluded that are using their natural resources efficiently.